1988
DOI: 10.2466/pms.1988.67.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Appreciation of Visual Art

Abstract: Summay.-For 37 participants, 16 men and 21 women, scores on the Tellegen Absorption Scale significantly correlated with liking for abstract paintings but not with liking for representational ones. After completing the scale, each participant viewed 20 paintings in quasirandom order, 10 of representational works and 10 of abstract ones. Each was rated on a scale from 1 for strongly disliked to 5 for strongly liked. The Pearson correlation of .48 for abstract paintings was significant, while that of .16 for repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Absorption has been linked to female gender, heightened creativity, hypnotisability, imagery-vividness, fantasy-proneness, and day-dreaming [ 49 51 ]. Artistic and aesthetic minded people seem to score higher on this questionnaire as well [ 52 54 ]. Individuals high in hypnotic susceptibility may be particularly sensitive to the automatic activation of cognitive and behavioral schemata by internal and external events [ 55 ], which could increase their vulnerability to developing somatoform symptoms [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absorption has been linked to female gender, heightened creativity, hypnotisability, imagery-vividness, fantasy-proneness, and day-dreaming [ 49 51 ]. Artistic and aesthetic minded people seem to score higher on this questionnaire as well [ 52 54 ]. Individuals high in hypnotic susceptibility may be particularly sensitive to the automatic activation of cognitive and behavioral schemata by internal and external events [ 55 ], which could increase their vulnerability to developing somatoform symptoms [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nell also argued that absorption should determine in part the desire and readiness of individuals for the attentional commitment of lucid reading. Similarly, the findings that absorption correlates with music enjoyment (Rhodes, David, & Combs, 1988;Snodgrass & Lynn, 1989) and art appreciation (Combs et al, 1988) point to the role of personal involvement of a cognitive or an emotional kind with the attentional object. Moreover, Fellows and Armstrong reported that subjects who scored low on absorption did not become involved in reading material provided by the experimenter but did become involved in reading material they chose themselves.…”
Section: Hypnosis and Hypnotizabilitymentioning
confidence: 93%
“…The psychiatrist Josephine Hilgard’s investigation of the associated construct of imaginative involvement (1970, 1974, 1979), which she linked with a tendency to become involved with some, but not other pastimes, was an important catalyst for the creation of the Tellegen Absorption scale (henceforth TAS, Tellegen & Atkinson, 1974). Using that measurement tool (a forced-choice, dichotomously-scored questionnaire containing 34 items), studies across a range of disciplines have correlated high levels of absorption with a selective yet diverse range of activities: these include religion (Levin, Wickramasekera, & Hirschberg, 1998), nature (Brown & Katcher, 1997; Kaplan, 1995), dancing (Bachner-Melman et al, 2005), reading (Nell, 1988), and art appreciation (Combs et al, 1988). Although some published studies claim that certain activities are inherently more absorbing than others, this appears a misguided assumption.…”
Section: Introductionmentioning
confidence: 99%
“…No studies of the experience of non-musical absorption in naturalistic settings have yet been attempted, and efforts to induce absorption in laboratory settings have tended to be rather artificial. For example, Combs et al (1988) used a 5-point Likert scale to assess liking of 20 slides of representational and abstract art, each of which was shown to participants for 10 seconds. Likert-scale scores were compared with TAS scores (completed before the slideshow), leading to the conclusion that high trait absorption scores “significantly correlated” with a preference for abstract art.…”
Section: Introductionmentioning
confidence: 99%